GUIDANCE AND COUNSELING PROGRAM MANAGEMENT IN THE STATEMADRASAH TSANAWIYAHTANJUNG BALAI - Lahmuddin Lubis; Marasamin Marasamin; Merry Andriany Hasibuan (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2019)
Researchresults show that 1. The planning has not appropriately implemented; this is indicatedby the guidance and counseling program that based on the analysis of the needs ofstudents, 2. Organizing is done quite well with the distribution of work tasks, 3.Actuating of activities carried out incidentally or in coordination with the subjectteacher, 4. Supervision/evaluation is not well implemented. This research concludes thatthe school will better understand the guidance and counseling activities by providingsupport facilities so that the program offered is following the needs of students.